Implicações da insônia e do tempo de duração do sono na redução da força neuromuscular e velocidade de caminhada em pessoas idosas: evidências do estudo ELSA - Silveira, Leticia Coelho (2024)
Introduction: The decline in neuromuscular strength (NS) and walking speed (WS) are associated with adverse outcomes in older adults, such as falls, hospitalizations, functional decline, and death. Although multifactorial, the decline in NS and WS appears to be influenced by insomnia symptoms and sleep duration. However, the little longitudinal evidence on the topic is controversial, and exploring this topic in studies with more extended follow-up periods is essential. Objectives: This dissertation has two objectives: 1) Analyze sex differences regarding the influence of sleep duration and insomnia symptoms on the trajectory of NS decline in people aged 50 or over during eight years of follow-up, and 2) Analyze the influence of sleep duration and insomnia symptoms on the trajectory of WS decline in people aged 60 or over during eight years of follow-up. Methods: Data came from the English Longitudinal Study of Aging (ELSA Study). To analyze the trajectory of NS decline, 6,429 participants aged 50 years or older with NS ≥ 27 kg for men and ≥ 16 kg for women were included. To analyze the trajectory of WS decline, 3,208 participants aged 60 years or over with WS > 0.8 m/s were included. In both studies, insomnia symptoms were assessed using the adapted and validated Jenkins questionnaire, and sleep duration was analyzed by self-report and classified as short (≤6 hours), ideal (>6 to <9 hours), and long (≥ 9 hours). Generalized linear mixed models estimated the decline rates of NS stratified by sex and WS in separate models as a function of insomnia symptoms and sleep duration and controlled for sociodemographic, behavioral, clinical, and anthropometric characteristics. Results: Regarding NS, over the eight years of follow-up, the greater number of insomnia symptoms was associated with a higher rate of NS decline in men (– 0.02 kg per year 95% CI – 0.04 – – 0. 01) while long sleep duration (≥ 9 hours) was associated with a higher rate of NS decline in women (– 0.14 kg per year 95%CI – 0.26 – – 0.03). Regarding WS, over the eight years of follow-up, only long sleep duration (≥ 9 hours) was associated with a higher rate of decline in WS (– 0.01 m/s per year 95% CI – 0.02 – – 0.01). Conclusion: Sleep changes influence the rate of NS decline differently between the sexes. In men, increased insomnia symptoms, while in women, long sleep duration (≥ 9 hours) increases the rate of NS decline in people aged 50 and over. As for WS, long sleep duration (≥ 9 hours) increases the risk of WS decline in people aged 60 years or older of both sexes.